Optoelectronic devices : design, modeling, and simulation - Li, Xun, Dr (Cambridge University Press, 2009)
With a clear application focus, this book explores optoelectronic device design and modeling through physics models and systematic numerical analysis. By obtaining solutions directly from the physics-based governing equations through numerical techniques, the author shows how to develop new devices and how to enhance the performance of existing devices. Semiconductor-based optoelectronic devices such as semiconductor laser diodes, electroabsorption modulators, semiconductor optical amplifiers, superluminescent light emitting diodes and their integrations are all covered. Including step-by-step practical design and simulation examples together with detailed numerical algorithms, this book provides researchers, device designers and graduate students in optoelectronics with the numerical techniques to obtain solutions for their own structures.